Pengaruh Lms Ruang Kelas Terhadap Hasil Belajar Peserta Didik Pada Pelatihan Wordpress Program Pendidikan 1 Tahun Prima Bina Insani Profesional - Muhammad Fuad Abdullah; Hj. Cheriani; Suhardiman (Berugak Baca, 2024)
This study aims to determine the effect of using the Learning Management System (LMS) Classroom on the learning outcomes of students in the Prima Bina Insani Professional 1-year education program. In this study the method used is quantitative. Quantitative methods are research in the form of numbers or numbers. Quantitative methods can be interpreted as research methods based on the philosophy of positivism, used to research on certain populations or samples, data collection using research instruments, data analysis is quantitative / statistical, with the aim of testing predetermined hypotheses. The t table value with a significant level = 0.05 and degrees of freedom (dk) = 28 from the distribution table obtained t table = 1.70113 with the results of the calculation of t count> t table or 8.32> 1.70113 thus Hₒ is rejected and H1 acceptance occurs. This shows that there is an effect of using learning media based on LMS Classroom on student learning outcomes in wordpress lessons in the Prima Bina Insani Professional 1 Year Education Program.